Composition characterization and biological activity study of achillea vermicularis extract and extract-loaded nanoparticles - YILMAZ SOYDAN, NACİYE TUBA; TAŞKIN, TURGUT (My University, 2023)
© 2023 International Union of Biochemistry and Molecular Biology, Inc.Antiproliferative activity of Achillea vermicularis extracts was calculated on glial (C6) and keratinocyte (HaCaT) cell lines using XTT assay. It was observed that all extracts of A. vermicularis at the determined concentration were not cytotoxic in HaCaT cell lines. The nanoparticles (NPs) of the extract with the best cytotoxic activity was prepared, and necessary characterization studies were performed. Results showed that NP containing the extract has a lower IC50 value and more cytotoxic activity in C6 cells compared to the only extract. Furthermore, the antiepileptic potentials of these substances were explored in this study. The effect of A. vermicularis extracts on the enzyme activities of carbonic anhydrase I and II isoenzymes (hCA I and hCA II) was measured using spectrophotometry to achieve this goal. A. vermicularis extracts demonstrated high inhibitory activities compared to standard inhibitor (acetazolamide, AAZ), with IC50 values in the range of 5.04–10.8 μg/ml for hCA I, and 5.40–9.22 μg/ml for hCA II. High-performance liquid chromatography diode array detector (HPLC-DAD) was used in this investigation to assess the main chemicals found in the extract and NPs. The results showed that the ethanol extract (157.636 μg/mg extract) and NPs (4.631 μg/mg extract) had a significant amount of the 8-hydroxy salvigenin component.
Keywords: Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Biomedical Engineering; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Chemistry; Other; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; Mikrobiyoloji; KİMYA, UYGULAMALI; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; CHEMISTRY, APPLIED; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Moleküler Tıp; Biyomedikal mühendisliği; Uygulamalı Mikrobiyoloji ve Biyoteknoloji; İlaç Keşfi; Proses Kimyası ve Teknolojisi; Bioengineering; Physical Sciences; Molecular Medicine; Applied Microbiology and Biotechnology; Drug Discovery; Process Chemistry and Technology; cytotoxic activity; encapsulation efficiency; enzyme inhibition